DIAGNOSTIC SIGNIFICANCE OF BONE MARROW EXAMINATION AMONGST THE PATIENTS WITH ABNORMAL HAEMATOLOGICAL PARAMETERS - Bashir, Saima; Fahim Akhtar; Misbah Salim; Maham Arshad; Zahra Tasleem Khan; Farhan Akhtar (Journal of Ayub Medical College Abbottabad, 2023)
Background: Bone Marrow examination is considered to be the most indispensable diagnostic tool for the evaluation of many neoplastic and non-neoplastic haematological disorders. After an initial assessment of suspicious cases on abnormal laboratory parameters along with the clinical presentation of the patient bone marrow examination is finally required for diagnosis as well as management of many haematological malignancies as it offers a clear cytological as well as histological picture of Bone Marrow aspirate and biopsy respectively. The Objective was to evaluate the significance of Bone Marrow examination in patients with abnormal haematological parameters. Methods: A retrospective study conducted at the Pathology Department of Pak Emirates Military Hospital from (Jan-June 2022) On data from 150 patients who were advised to undergo bone marrow examination due to abnormal lab parameters and peripheral smear findings after informed consent and approval from the ethics review committee, to find out the correlation of abnormal haematological parameters and aspirate findings which have led to a definitive diagnosis. Data comprising basic demographic variables (age, gender etc.), Abnormal Haematological Parameters (CBC), peripheral smear findings and Aspirate findings were analyzed using SPSS version 23.0. Results: Out of 150 studied participants with abnormal haematological parameters 24 (16%) were diagnosed on bone marrow examination as acute leukaemia / Hodgkin’s and Non-Hodgkin’s lymphoma respectively, 13 (9%) cases of aplastic anaemia and Autoimmune Haemolytic Anaemia, 33 (22%) cases of hypersplenism, CML and multiple myeloma. While 22 (15%) cases were diagnosed with BME as CKD and reactive changes. Moreover, 22(15%) cases were found to have Iron Deficiency anaemia respectively. Conclusion: The study revealed that patients with abnormal haematological parameters should undergo bone marrow examination to ascertain the diagnosis for malignant as well as non-malignant conditions that could cause abnormal lab parameters.